2015
DOI: 10.1097/md.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection Improves the Outcome of the Patients With Neuroendocrine Tumor Liver Metastases

Abstract: How to properly manage neuroendocrine liver metastasis (NELM) remains debatable, and only limited clinical data have been published from Asian population. The objective of this study is to identify possible prognostic factors affecting overall survival time and to provide a guideline for future clinical practice.A retrospective study was performed on 1286 patients who had neuroendocrine tumors in our specialized center, and data from 130 patients who had NELM were summarized. Demographic and clinicopathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 30 publications
5
35
1
Order By: Relevance
“…To achieve curative intent, the complete removal of primary and metastatic tumors should be considered. Earlier studies have found that PTR improved the 5‐year OS rates of patients, ranging from 33.3% to 74.0%, irrespective of tumor function . Consistent with these results, compared to the nonresection group, an improvement in 5‐year OS rates (from 15.4% to 57.0%) was observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To achieve curative intent, the complete removal of primary and metastatic tumors should be considered. Earlier studies have found that PTR improved the 5‐year OS rates of patients, ranging from 33.3% to 74.0%, irrespective of tumor function . Consistent with these results, compared to the nonresection group, an improvement in 5‐year OS rates (from 15.4% to 57.0%) was observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a retrospective study by Tierney et al showed significantly prolonged survival of patients with metastatic disease who underwent PTR . Nevertheless, this study did not make a distinction between LM and other sites of metastases, and several studies that support PTR were limited by their small sample size and the analysis of a single primary site …”
Section: Introductionmentioning
confidence: 91%
“…Liver metastases accounts for about 90% of the distant metastases of PNET and is a major prognostic factor for this tumor [2,10,11]. Previous researchers have reoprted that the concurrent resection of both the primary lesion and resectable liver metastases is feasible and might improve the prognosis [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is associated with the overexpression of both ligand and related receptor of vascular endothelial factor (VEGF) (63), particularly in hepatic metastases (64). Sunitinib is an oral, smallmolecule, multi-targeted tyrosine kinase inhibitor with activity against VEG-F and PDGF.…”
Section: Agents For Antiangiogeneismentioning
confidence: 99%